Campomanesia adamantium (Cambess.) O. Berg seed desiccation: influence on vigor and nucleic acids - DAIANE M. DRESCH; TATHIANA E. MASETTO; SILVANA P.Q. SCALON (Anais da Academia Brasileira de Ciências, 2015)
The aim of this study was to evaluate the sensitivity of Campomanesia adamantium seeds to desiccation by drying in activated silica gel (fast) and under laboratory conditions (slow). To assess the sensitivity of the seeds to desiccation, we used drying with silica gel and drying under laboratory conditions (25 °C), in order to obtain seeds with moisture content of 45, 35, 30, 25, 20, 15, 10 and 5%. The physiological potential of the seeds after desiccation was evaluated by measuring primary root protrusion, percentage of normal seedlings, germination seed index, seedling length, total seedling dry mass, electrical conductivity and DNA and RNA integrities. The C. adamantium seeds were sensitive to desiccation and to a reduction in moisture content to 21.1% or less by desiccation using silica gel, and to 17.2% or less by desiccation under laboratory conditions; impairment of the physiological potential of the seeds was observed at these low moisture content levels. The integrity of the seed genomic DNA was not affected after drying seeds in the two methods. However, drying in silica gel to 4.5% moisture content and drying under laboratory conditions to 5.4% moisture content resulted in the loss of seed RNA integrity.